THE IMPACT OF FLUCTUATIONS IN THE INTERNATIONAL OIL MARKETS ON THE IRAQI ECONOMY (World Economics and Finance Bulletin, 2024)
Oil revenues play a significant role in the Iraqi economy, whether it is through its contribution to the formation of the GDP or its contribution to total exports as well as financing public expenditures and providing foreign reserves. However, the dependence of the Iraqi economy almost entirely on oil revenues had negative effects on the Iraqi economy, as the Iraqi economy is directly proportional to oil prices in international markets, so the Iraqi economy thrives with rising prices and declines with their decline. This poses a great danger to the Iraqi economy and works to destabilize it